2021
DOI: 10.2298/vsp190916129d
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia and inflammatory biomarkers are associated with higher clinical SYNTAX score in patients with stable coronary artery disease

Abstract: Background/Aim. Previous studies have confirmed a positive correlation between homocysteine levels and a greater risk for acute coronary syndrome and stroke, but there are no available data to support an association between homocysteine and inflammatory markers and the severity of coronary artery disease according to Clinical SYNTAX score in patients with stable angina. The aim was to determine the association between homocysteine and inflammatory biomarkers levels: interleukin 6, high sensitive C reactive pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Several studies have shown that folic acid and vitamin B12 supplementation can lower Hcy concentration [70], and supplementation with folic acid can improve damaged vascular endothelial function in CAD [71]. HHcy is also positively correlated with the severity of CAD [72]. Another study showed a positive correlation between Hcy level and CAD, as well as significant negative correlation between Hcy levels and folic acid concentration in all CAD categories [66].…”
Section: Homocysteine and Cvdmentioning
confidence: 99%
“…Several studies have shown that folic acid and vitamin B12 supplementation can lower Hcy concentration [70], and supplementation with folic acid can improve damaged vascular endothelial function in CAD [71]. HHcy is also positively correlated with the severity of CAD [72]. Another study showed a positive correlation between Hcy level and CAD, as well as significant negative correlation between Hcy levels and folic acid concentration in all CAD categories [66].…”
Section: Homocysteine and Cvdmentioning
confidence: 99%